A comparative analysis of in vitro antioxidant potential of crude extracts of Tridax procumbens L. in different solvents and in vitro hypoglycemic potential of its hydro-alcoholic extract - Smita Nair; Savita Dixit; N . Ganesh (Mazandaran University of Medical Sciences, 2016)
The therapeutic potential of crude extracts of aerial parts (stem, leaves and flowers) of Tridax procumbens was screened for in vitro antioxidant potential and alpha amylase inhibitory action. The crude hydro-methanolic, aqueous and petroleum ether extracts were obtained by percolation-maceration method using 50% methanol, double distilled water and petroleum ether as solvents. Phytochemical screening of these extracts revealed the presence of flavonoids, tannins, alkaloids, glycosides, saponins, phenols, steroids and carbohydrate. Antioxidant activities of the extracts were evaluated for free radical scavenging by hydrogen peroxide scavenging and superoxide scavenging potential. The in vitro alpha amylase inhibition action of hydro-methanolic extract of aerial parts of the plant (HMETP) was evaluated for hypoglycemic properties using starch as substrate. Mode of inhibition of the enzyme was also determined. The results indicated that hydro-methanolic extract showed significant antioxidant potency at concentration of 25-80 μg as compared to aqueous and petroleum ether extracts and also possess alpha amylase inhibitory property. Hence it can be suggested that hydroalcoholic extract of aerial parts of Tridax procumbens has potential as an antioxidant and probably in biological systems as a nutraceutical for hypoglycemia.